Code Switching and Code Mixing Analysis Uttered by Cinta Laura on Helmy Yahya Bicara Podcast - Maretha, Dina Rizki (Politeknik Negeri Sriwijaya, 2023)
ABSTRACT: The objectives of this final report were to find out the types of code switching and code mixing. This final report focuses in analysis Cinta Laura’s utterances in Helmy Yahya Bicara Podcast which contained code switching and code mixing in the audio as the data of this final report. Steps taken by the writer in completing this final report was watching a YouTube, downloaded a YouTube video, listen the speech in the video and transcribe the utterance into a script which is required as a data, then the data were analyzed with descriptive qualitative method. The result of this final report found that there are three types of code switching and two types of code mixing. Code switching contained tag-switching which occured 9 data, intra-sentential switching 44 data, and inter-sentential switching 25 data. Code mixing contained insertion which occurred 80 data and alternation 4 data. The writer expects that this final report can give more information and enlarge knowledge about bilingualism, code switching, and code mixing especially for English Department at State Polytechnic of Sriwijaya. Keywords: Code Switching, Code Mixing, Bilingualism